Recent Advances in Electrophysiological Recording Platforms for Brain and Heart Organoids. Issue 12 (20th November 2022) - Chung, Won Gi; Kim, Enji; Song, Hayoung; Lee, Jakyoung; Lee, Sanghoon; Lim, Kyeonghee; Jeong, Inhea; Park, Jang-Ung
Abstract : Organoids refer to 3D stem cells that have been developed to model neurological disorders in vitro. Typically, brain and heart organoids have gained interest for their potential to truly mimic the functional ability of real organs. Morphological analysis methods using immunostaining and slicing of the organoids are explored extensively over the past decade to evaluate the structures and functions of organoids. However, the destructiveness of these methods limits real‐time monitoring of the dynamic responses of the organoids. Therefore, electrophysiological functional analysis of organoids with minimally invasive forms can be a key solution to an improved understanding of the nature of complex organoids. Herein, the latest advances in the recording platforms are reviewed and a comprehensive study of considerations regarding electrophysiological factors is provided. Furthermore, current challenges are discussed along with prospects for next‐generation electrophysiological analysis of brain and heart organoids. Abstract : Recent remarkable advances in brain and heart organoid engineering are discussed. For the precise evaluation of these organoids, electrophysiological functional analysis must be conducted. Various methods to grasp these electrophysiological signals are discussed in this review with perspectives on the future direction of organoid biosensing platforms such as flexible, soft electronics to complex analysis methods.